Soil fertility management for yield and income stability in soybean-wheat rotation system under climate variability in subtropical Central India - Shinogi K. C.; Sanjay Srivastava; Radha T. K.; D. L. N. Rao; Bharat Prakash Meena; Nishant Kumar Sinha; Hiranmoy Das; Rashmi I.; Rosin K. G.; Amar Bahadur Singh; Sanjib Kumar Behera; Monoranjan Mohanty (PLoS ONE, 2026)
The soybean–wheat rotation system forms a crucial component of Central India’s rainfed agriculture. Although historically productive and profitable, the system’s sustainability is increasingly threatened by suboptimal nutrient management, and soil degradation under changing climate. This three-year study, conducted on small and semi-medium farms in Central India using a Participatory Technology Development (PTD) approach, aimed to evaluate how diverse nutrient management strategies influence yield, profitability, and resource use efficiency. Four nutrient management strategies were tested on small to semi-medium farms: (T 1 ) Integrated Nutrient Management (INM) using chemical fertilizers, farmyard manure and biofertilizers, (T 2 ) Integrated Nutrient Management using chemical fertilizers, enriched compost and biofertilizers, (T 3 ) Soil test crop response-based fertilization, and (T 4 ) Farmers’ conventional practice. Among the four treatments T 2 achieved the highest system productivity (6.63 t ha ⁻ ¹ wheat equivalent), net returns (67,680 INR ha ⁻ ¹), and superior yield stability, under climatic variability. T 3 offered moderate productivity while promoting balanced nutrient use and lower input costs. Both T 2 and T 3 enhanced microbial activity and soil health, while T 4 led to nutrient depletion, (especially potassium), and low returns. Furthermore, the timing and distribution of monsoon rainfall significantly impacted performance and yield stability of soybean. This study highlights the critical need for integrated, site-specific, and farmer-centric nutrient management strategies to ensure sustainable productivity, profitability, and soil health under changing climatic conditions.